The differentiation of prehypertrophic into hypertrophic chondrocytes drives an OA-remodeling program and IL-34 expression. Issue 2 (February 2021) - van Eegher, S.; Perez-Lozano, M.-L.; Toillon, I.; Valour, D.; Pigenet, A.; Citadelle, D.; Bourrier, C.; Courtade-Gaïani, S.; Grégoire, L.; Cléret, D.; Malbos, S.; Nourissat, G.; et al.
Summary: Objectives: We hypothesize that chondrocytes from the deepest articular cartilage layer are pivotal in maintaining cartilage integrity and that the modification of their prehypertrophic phenotype to a hypertrophic phenotype will drive cartilage degradation in osteoarthritis. Design: Murine immature articular chondrocytes (iMACs) were successively cultured into three different culture media to induce a progressive hypertrophic differentiation. Chondrocyte were phenotypically characterized by whole-genome microarray analysis. The expression of IL-34 and its receptors PTPRZ1 and CSF1R in chondrocytes and in human osteoarthritis tissues was assessed by RT-qPCR, ELISA and immunohistochemistry. The expression of bone remodeling and angiogenesis factors and the cell response to IL-1β and IL-34 were investigated by RT-qPCR and ELISA. Results: Whole-genome microarray analysis showed that iMACs, prehypertrophic and hypertrophic chondrocytes each displayed a specific phenotype. IL-1β induced a stronger catabolic effect in prehypertrophic chondrocytes than in iMACs. Hypertrophic differentiation of prehypertrophic chondrocytes increased Bmp-2 (95%CI [0.78; 1.98]), Bmp-4 (95%CI [0.89; 1.59]), Cxcl12 (95%CI [2.19; 5.41]), CCL2 (95%CI [3.59; 11.86]), Mmp 3 (95%CI [10.29; 32.14]) and Vegf mRNA expression (95%CI [0.20; 1.74]). Microarray analysis identified IL-34, PTPRZ1 and CSFR1 as being strongly overexpressed in hypertrophic chondrocytes. IL-34 was released by human osteoarthritis cartilage; its receptors were expressed in human osteoarthritis tissues. IL-34 stimulated CCL2 and MMP13 in osteoblasts and hypertrophic chondrocytes but not in iMACs or prehypertrophic chondrocytes. Conclusion: Our results identify prehypertrophic chondrocytes as being potentially pivotal in the control of cartilage and subchondral bone integrity. Their differentiation into hypertrophic chondrocytes initiates a remodeling program in which IL-34 may be involved.